Dinamika Negoisasi GAM dan RI di Helsinki - Risky Novialdi M.IR (Budapest International Research and Critics University, 2017)
The articles disclosed on the peace agreement between GAM and the RI is not an easy journey, but it requires the preparation of good strategies and iknikad so as to create an effective negotiation forum. In the negotiation phase requires maturity and experience starting from the exploratory stage, the selection of mediators, until the commitment after the deal. This is what both GAM and RI have achieved in reaching a peace agreement. Aceh's dark sheet has been closed, now the new sheet has been opened since 2005 ago. Now is the time for Aceh to lead and manage its own territory with